Assessing COVID-19 Vaccine Side Effects: A Comparative Study of Partial and Fully Vaccinated Population in Lahore, Pakistan - NIda Shehzadi, Hafiza; Islam Butt, Hamama; Abbas, Saba; Khawar, Hafiz; Murtaza, Misbah; Akram, Madiha; Mohsin Zaheer, Muhammad; Muhammad Azeem, Hafiz (Pakistan Journal of Medical & Health Sciences, 2024)
Background: Vaccines provide immunity to minimize disease progression by enhancing adaptive immunity in the body, with mild to moderate side effects after immunization. Aim: To evaluate the side effects of COVID-19 immunization among partially and fully vaccinated participants in Lahore. Study design: The randomized survey-based study was conducted at Minhaj University Lahore, Pakistan, from October 1st to December 31st, 2022. Methods: Utilizing a questionnaire to collect data on the side effects experienced by participants after receiving the COVID-19 vaccine. Participants were aged 16-65 age who had received either partial or full doses of COVID-19 vaccine, representing the population of Punjab, Pakistan. Result: Data revealed that 90.1% of respondents received a full vaccine, whereas 9.8% received a partial/single dose respectively. However, in fully vaccinated participants 41.1% developed fever and fatigue symptoms, 14.1% nausea and sneezing, 11.3% GIT disturbance, 10.5% rigors, and 7.4% shortness of breath. However, in partially immunized participants, 58.9% developed fever, 44.6% soreness, 19.6 nausea, 57.1% fatigue, 55.3% sneezing, 39.2% GIT disturbance, 39.2% rigors, and 32.1% shortness of breath respectively. The mean value of the percentage of partially vaccinated people was around 40.3 in comparison to the fully vaccinated people which was 22.6. The study found that partially vaccinated individuals experienced significantly higher side effects (p=0.019) than fully vaccinated individuals, and most participants experienced minor to moderate side effects after partial and full COVID-19 vaccinations. Practical implication: The findings of this study underscore the importance of developing single-dose vaccines with reduced side effects and enhanced immune response, providing valuable insights for future vaccine research and development efforts. Conclusion: The results emphasize to researchers to give greater consideration to the development of single-dose vaccines with fewer side effects and with more improved immune response.